The Alma Survey of Gas Evolution of Protoplanetary Disks (Age-Pro). Iv. Dust and Gas Disk Properties in the Upper Scorpius Star-Forming Region - Miley, J; Gonzalez-Ruilova, C (Institute of Physics, 2025)
The Atacama Large Millimeter/submillimeter Array (ALMA) large program AGE-PRO explores protoplanetary disk evolution by studying gas and dust across various ages. This work focuses on 10 evolved disks in Upper Scorpius, observed in dust continuum emission, CO and its isotopologues, and N2H+ with ALMA Bands 6 and 7. Disk radii, from the radial location enclosing 68% of the flux, are comparable to those in the younger Lupus region for both gas and dust tracers. However, solid masses are about an order of magnitude below those in Lupus and Ophiuchus, while the dust spectral index suggests some level of dust evolution. These empirical findings align with a combination of radial drift, dust trapping, and grain growth into larger bodies. A moderate correlation between CO and continuum fluxes suggests a link between gas and dust content, through the increased scatter compared to younger regions, possibly due to age variations, gas-to-dust ratio differences, or CO depletion. Additionally, the correlation between C18O and N2H+ fluxes observed in Lupus persists in Upper Scorpius, indicating a relatively stable CO gas abundance over the Class II stage of disk evolution. In conclusion, the AGE-PRO survey of Upper Scorpius disks reveals intriguing trends in disk evolution. The findings point toward potential gas evolution and the presence of dust traps in these older disks. Future high-resolution observations are needed to confirm these possibilities and further refine our understanding of disk evolution and planet formation in older environments. © 2025. The Author(s). Published by the American Astronomical Society.